147k views
4 votes
Let f(x) = 4x – 2 and g(x) = x + 1. Find the following function value.
(f - g)(-3)

User Jtabuloc
by
5.8k points

1 Answer

3 votes

Answer:

(f - g)(3) = 6

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS

Algebra I

  • Function Notation

Explanation:

Step 1: Define

f(x) = 4x - 2

g(x) = x + 1

Step 2: Find

Find (f - g)(x)

  1. Substitute: (f - g)(x) = 4x - 2 - (x + 1)
  2. Distribute -1: (f - g)(x) = 4x - 2 - x - 1
  3. Combine like terms: (f - g)(x) = 3x - 3

Find (f - g)(3)

  1. Substitute: (f - g)(3) = 3(3) - 3
  2. Multiply: (f - g)(3) = 9 - 3
  3. Subtract: (f - g)(3) = 6
User Ssekhar
by
5.9k points